Structural mechanism underpinning Thermus oshimai Pif1‐mediated G‐quadruplex unfolding. (23rd June 2022) - Dai, Yang‐Xue; Guo, Hai‐Lei; Liu, Na‐Nv; Chen, Wei‐Fei; Ai, Xia; Li, Hai‐Hong; Sun, Bo; Hou, Xi‐Miao; Rety, Stephane; Xi, Xu‐Guang
Abstract: G‐quadruplexes (G4s) are unusual stable DNA structures that cause genomic instability. To overcome the potential barriers formed by G4s, cells have evolved different families of proteins that unfold G4s. Pif1 is a DNA helicase from superfamily 1 (SF1) conserved from bacteria to humans with high G4‐unwinding activity. Here, we present the first X‐ray crystal structure of the Thermus oshimai Pif1 ( To Pif1) complexed with a G4. Our structure reveals that To Pif1 recognizes the entire native G4 via a cluster of amino acids at domains 1B/2B which constitute a G4‐Recognizing Surface (GRS). The overall structure of the G4 maintains its three‐layered propeller‐type G4 topology, without significant reorganization of G‐tetrads upon protein binding. The three G‐tetrads in G4 are recognized by GRS residues mainly through electrostatic, ionic interactions, and hydrogen bonds formed between the GRS residues and the ribose‐phosphate backbone. Compared with previously solved structures of SF2 helicases in complex with G4, our structure reveals how helicases from distinct superfamilies adopt different strategies for recognizing and unfolding G4s. Synopsis: The X‐ray crystal structure of the ToPif1 helicase complexed with a G‐quadruplex DNA (G4) mimicking the physiological G4 formed during DNA replication reveals molecular aspects of helicase‐mediated G‐quadruplex unfolding. ToPif1 unfolds G4 in an ATP‐dependent manner without topological preference. ToPif1 binds the integral G4 structure without a G4‐specific targeting motif. ToPif1 recognizes the entire native G4 via a G4‐Recognizing Surface (GRS) which exhibits different interactions with different tetrads showing that helicases from distinct superfamilies adopt different strategies for recognizing and unfolding G4s. Abstract : The crystal structure of ToPif1 complexed with a G4 shows that ToPif1 recognizes the entire native G4 via a G4‐Recognizing Surface. It reveals how helicases from distinct superfamilies use different strategies for recognizing and unfolding G4s.